Preliminary analysis on the aura of female before and after performing ablution (wudu') by using Resonant Field Imaging (RFI) / Noradilah Alias - Alias, Noradilah (2011)
This research presents an analysis on the aura of human body before and after performing ablution by using Resonant Field Imaging (RFI) system. The objectives are to analyze the aura of human body before and after performing ablution and analyze whether performing ablution can give good effect to human body. The measurement was taken from 30 female samples around 2 minutes before and after performing ablution. The data collected was analyzed by translating into the color of aura with different score. The result show that 67% of the sample does improve of human body aura after performing ablution. The analysis by region also shows that excellent and good category does improve. Based on the result presented, it can be concluded that the human body aura does improve significantly by performing ablution.